2021
DOI: 10.25270/wnds/2021.e90e92
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chancre-Variant Cutaneous Tuberculosis After BCG Vaccine Administration in a Patient With Migraines

Abstract: In countries other than the United States, the BCG vaccine is typically used as a method for preventing childhood tuberculosis; in the United States, the BCG vaccine has gained popularity as a speculated therapy for autoimmune and inflammatory disorders. Research suggests that the vaccine can train the innate immune response, thereby improving symptoms of disorders such as diabetes and fibromyalgia. However, the potential side effects associated with the use of this vaccine are not totally innocuous. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Most recipients of the BCG vaccine report a benign and localized skin reaction after administration, although there is a risk for more serious cutaneous side effects such as fistulation, abscess formation, and ulceration. Even rarer, a tuberculous chancre can form with inoculation of M. bovis to the skin after local trauma, and this accounts for about 1–2% of CTB [ 52 ]. Multiple reports have been published describing the extremely rare development of a CTB reaction after the administration of the BCG vaccination [ 17 ].…”
Section: Clinical Presentation Of Ctbmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recipients of the BCG vaccine report a benign and localized skin reaction after administration, although there is a risk for more serious cutaneous side effects such as fistulation, abscess formation, and ulceration. Even rarer, a tuberculous chancre can form with inoculation of M. bovis to the skin after local trauma, and this accounts for about 1–2% of CTB [ 52 ]. Multiple reports have been published describing the extremely rare development of a CTB reaction after the administration of the BCG vaccination [ 17 ].…”
Section: Clinical Presentation Of Ctbmentioning
confidence: 99%
“…Dhar et al describe a previously healthy 4-month-old diagnosed with biopsy-confirmed disseminated CTB at the site of BCG immunization that resolved without recurrence after anti-TB treatment [ 17 ]. A case report conducted by Stratmen et al described an adult developing chancre-variant CTB in response to receiving the BCG vaccine for the treatment of fibromyalgia [ 52 ]. The patient underwent surgical debulking of the chancre as well as 6 months of Isoniazid monotherapy, and the complication resolved.…”
Section: Clinical Presentation Of Ctbmentioning
confidence: 99%
“…Similarly, on histology, granulomatous dermatitis is present, and staining for Mycobacteria bovis is positive. 34 Surgical debulking of the area may be necessary in addition to 6 months of anti-tuberculosis drugs. 34 …”
Section: Introductionmentioning
confidence: 99%
“… 34 Surgical debulking of the area may be necessary in addition to 6 months of anti-tuberculosis drugs. 34 …”
Section: Introductionmentioning
confidence: 99%